2017
DOI: 10.2147/hmer.s125718
|View full text |Cite
|
Sign up to set email alerts
|

PNPLA3 expression and its impact on the liver: current perspectives

Abstract: A single-nucleotide polymorphism occurring in the sequence of the human patatin-like phospholipase domain-containing 3 gene (PNPLA3), known as I148M variant, is one of the best characterized and deeply investigated variants in several clinical scenarios, because of its tight correlation with increased risk for developing hepatic steatosis and more aggressive part of the disease spectrum, such as nonalcoholic steatohepatitis, advanced fibrosis and cirrhosis. Further, the I148M variant is positively associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
4

Year Published

2019
2019
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 90 publications
2
63
0
4
Order By: Relevance
“…A volcano plot demonstrates that the genes significantly down‐regulated by Elovl6 deficiency (Supporting Fig. D) included patatin‐like phospholipase domain containing 3 ( Pnpla3 ), which encodes a membrane‐bound protein with a predominant TAG lipase activity . Quantitative real‐time PCR analysis confirmed that Pnpla3 expression was increased 67‐fold by HSD feeding in the liver of Flox mice and reduced by 68% in the liver of LKO mice (Fig.…”
Section: Resultsmentioning
confidence: 81%
“…A volcano plot demonstrates that the genes significantly down‐regulated by Elovl6 deficiency (Supporting Fig. D) included patatin‐like phospholipase domain containing 3 ( Pnpla3 ), which encodes a membrane‐bound protein with a predominant TAG lipase activity . Quantitative real‐time PCR analysis confirmed that Pnpla3 expression was increased 67‐fold by HSD feeding in the liver of Flox mice and reduced by 68% in the liver of LKO mice (Fig.…”
Section: Resultsmentioning
confidence: 81%
“…PNPLA3 is a member of a family of patatin‐domain containing lipid hydrolases with specificity for an array of different substrates, including triacylglycerols, phospholipids and retinol esters 106 . PNPLA3 expression levels are highest in hepatocytes and hepatic stellate cells in humans and in adipocytes in mice, followed by the retina and other tissues in both species 22 . High carbohydrate levels upregulate PNPLA3 levels in mice 107,108 and in human hepatocytes 109,110 by increasing transcription and reducing protein turnover.…”
Section: Pnpla3 Precision Medicine In Patients With Nashmentioning
confidence: 99%
“…Insulin and retinol regulate PNPLA3 expression. The PNPLA3 I148M mutation leads to the loss of enzymatic activity and subsequent changes in triglyceride metabolism and is associated with ALD, non-alcoholic fatty liver disease (NAFLD), and HCC [42]. The role of this mutation in the alterations in retinol metabolism is less clear.…”
Section: Hepatic Stellate Cellsmentioning
confidence: 99%